Physicochemical, Phytochemical and Microscopical Studies on Tridax Procumbens Linn. - Kumar, Shankul (International Journal of Pharmaceutical & Biological Archive, 2011)
ABSTRACTTridax procumbens Linn. is a wild plant, found as weed throughout India. The plant is native of tropical America and naturalized in tropical Africa, Asia, and Australia. Local people knew it as ?óÔé¼?ôGhamara?óÔé¼?Ø, in English popularly called ?óÔé¼?£coat buttons?óÔé¼Ôäó and is dispensed for ?óÔé¼?ôBhringraj?óÔé¼?Ø by some of the practitioners for hair growth in Ayurveda1. The Present studies give pharmacopoeial standards like physical constant (LOD, Ash value and Extractive value), leaf constant (stomatal number, stomatal index, palisade ratio, vein-islet number and vein termination number) and cellular characteristics of the plant parts. The phytochemical screening revealed the presence of alkaloids, carotenoids, flavonoids, fumaric acid, ?Ä??-sitosterol, saponins and tannins.